Pengaruh Green HRM dan Dukungan Organisasi Terhadap Tingkat Retensi Karyawan Melalui Keterlibatan, Kepuasan Kerja, dan Komitmen Afektif Di UKM Manufaktur - Dicky Wisnu Usdek Riyanto (Jurnal Manajerial, 2025)
Background – The business world is increasingly focusing on sustainability and environmentally friendly human resource management. The practice of Green Human Resource Management (Green HRM) is a crucial strategy for enhancing the image of a socially and environmentally responsible organization. Green HRM not only fosters concern for the environment but also shapes pro-environmental behavior in the workplace, enhances employee engagement, and increases job satisfaction, ultimately affecting employee retention. Aim – This study aims to analyze the influence of Green Human Resource Management (Green HRM) and Organizational Support on employee retention rates in manufacturing small and medium-sized enterprises (SMEs), examining both direct and indirect effects through the mediating roles of work engagement, job satisfaction, and affective commitment. Design/ Methodology/ Approach – This study employs a quantitative approach with a survey design to investigate the relationship between Green Human Resource Management (GHRM), Organizational Support, Affective Commitment, and Employee Retention in manufacturing SMEs in Malang. The research sample consisted of 149 permanent employees, selected using purposive sampling based on specific criteria. Data was collected through an online questionnaire with a 5-point Likert scale. The research instrument has been tested for validity and reliability. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the direct and indirect relationships between variables in the research model. Findings – This study found that Green HRM has a positive and significant effect on employee affective commitment, and affective commitment has a positive effect on employee retention. However, the direct influence of Green HRM on employee retention is not significant without the mediation of affective commitment. In contrast, organizational support has no significant effect on affective commitment or employee retention. These findings confirm that employee emotional commitment is a key factor in strengthening the relationship between Green HRM practices and employees' decisions to stay in the company. Conclusion – This research emphasizes the importance of developing sustainability-based human resource management strategies to strengthen employee emotional attachment, which ultimately supports efforts to retain the workforce in the manufacturing SME sector. Research implication – This research suggests that Green HRM practices are effective in increasing employee retention through affective commitment. In the future, management studies should focus more on integrating sustainability into human resource (HR) strategies to enhance organizational loyalty and competitiveness. Limitations – The variables analyzed only included Green HRM, organizational support, engagement, job satisfaction, and affective commitment, so other factors that may affect employee retention, such as leadership style or organizational culture, have not been explored.